Asymptotic Expansion of Solutions to Singular Perturbation Problems in Critical Cases (Journal of Nonlinear Modeling and Analysis, 2024)
This paper investigates the problem of singular perturbed integralinitial values and Robin boundary values in the critical case. Based on theboundary layer function method, we not only construct the asymptotic approximation of the original equation, but also prove the uniform validity ofthe asymptotic solution by successive approximation. At the same time, wegive an example to prove the validity of the theoretical results.
Keywords: Singularly perturbed problem; critical case; boundary function method; approximate solution.